Psychobiological Mechanisms of Resilience in the Pesantren Ecology: A Comparative Structural Equation Modeling of Distress, Coping, and Salivary Cortisol between Boarding and Non-Boarding Santri in East Java - Winata Putri; Irna Nettles; Theresia Putri Sinaga; Vidhya Sathyakirti; Sari Sulistyoningsih (HM Publisher, 2025)
Introduction: The Pesantren (Islamic boarding school) represents a unique educational ecosystem in Indonesia that imposes distinct psychosocial demands on students (Santri). While the academic outcomes of this system are well-documented, the psychobiological divergences between boarding (Mukim) and non-boarding (Kalong) students regarding stress adaptation remain under-researched. Methods: This cross-sectional comparative study involved 500 adolescents (ages 15-18) from four large Pesantrens in East Java, stratified into Boarding (n = 250) and non-boarding (n = 250) groups. Participants completed the Kessler Psychological Distress Scale (K-10), the Connor-Davidson Resilience Scale (CD-RISC-25), and the Brief-COPE. Additionally, morning salivary cortisol samples were collected to assess hypothalamic-pituitary-adrenal (HPA) axis activity. Data were analyzed using MANCOVA and Structural Equation Modeling (SEM). Results: Boarding students exhibited significantly higher baseline psychological distress (p < 0.001) and elevated cortisol levels compared to non-boarders. However, they also demonstrated significantly higher resilience scores and utilization of adaptive religious coping strategies. SEM analysis revealed that while boarding status is a predictor of physiological stress, its impact on psychological distress is fully mediated by adaptive coping mechanisms and community integration. Conclusion: Boarding students face heightened physiological stress loads but possess superior compensatory resilience mechanisms driven by religious coping. Interventions should focus on strengthening these adaptive pathways.